Feasibility Study Of A Grid Tied PV System For Universiti Teknikal Malaysia Melaka - Mohd Yassim, Halyani; Gan, Chin Kim; Hussin, Mohamed Saiful Firdaus; Jaafar, Rohaina; Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat (Asian Research Publishing Network (ARPN), 2020)
Universiti Teknikal Malaysia Melaka (UTeM) has to consider renewable energy as part of electricity generation to save cost of electricity. Photovoltaic (PV) system hereof is appropriate because it is reliable for sunny location like Melaka. Therefore, the purpose of this research is to carry out feasibility study of providing electricity from PV system for UTeM. The proposed system comprises of grid tied PV and battery storage. The techno-economic analysis of the proposed system was performed using Hybrid Optimization of Multiple Energy Resources (HOMER) software. The optimal size and the cost-effective configurations of the system were identified. From the simulation result, the optimal grid tied PV system has the minimum net present cost (NPC) and economic benefits over base system (utility grid) with 16.6% internal rate of return (IRR) and 5.7 years payback period. The results obtained can be used as references for the stakeholders and policy makers in developing grid tied PV system for university campuses